Fertilization Management to Improve Stockpiled Tall Fescue in the Fall - B. C. Pedreira; D. Helwig; M. Haywood; J. K. Farney; G. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2022)
In 2019 and 2021, a tall fescue fertility study was conducted at the K-State Experiment Station near Columbus, KS. The purpose of the study was to determine the effect of summer fertilization on forage quality and quantity in stockpiled fescue. If a producer can stockpile high-quality forage for late fall and early winter grazing, protein supplementation may not be necessary for fall calving cows.
Keywords: Fertilizer; perennial grass; forage quality; crude protein; total digestible nutrients